Pengaruh Gaya Kepemimpinan Transformasional, Budaya Organisasi dan Motivasi terhadap Kinerja Karyawan Pada Indomaret Cabang Gading Serpong Tangerang Selatan - Sari, Ratna (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study aims to examine and analyze the influence of transformational leadership style, organizational culture, and motivation on employee performance at Indomaret Gading Serpong Branch. The research adopts an associative approach with a quantitative method. The sample consists of 80 respondents. Data analysis techniques include validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, simple linear regression, multiple linear regression, coefficient of determination, t-test, and F-test. The results indicate that transformational leadership style has a positive and significant influence on employee performance. Organizational culture also contributes positively and significantly to employee performance. Furthermore, motivation is found to have a positive and significant effect on employee performance. Additionally, transformational leadership style, organizational culture, and motivation collectively have a positive and significant impact on employee performance. The simultaneous contribution of these three variables to employee performance demonstrates the importance of leadership, organizational culture, and motivation in enhancing work outcomes. This research highlights the crucial role of leadership style in shaping employee performance, as well as the impact of a strong organizational culture and motivation in driving employees to achieve better results. The findings suggest that companies should focus on developing transformational leadership, fostering a supportive organizational culture, and enhancing motivation to improve overall employee performance.